A Bimetallic Lanthanide Metal-Organic Material as a Self-Calibrating Color-Gradient Luminescent Sensor - Zhou, Jingmin (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.